Synergistic action between extracellular products from white-rot fungus and cellulase significantly improves enzymatic hydrolysis. Issue 1 (1st January 2018) - Wang, Yushan; Shao, Yang; Zou, Xinyue; Yang, Mandi; Guo, Lin
ABSTRACT: With a set of perfect extracellular lignocellulolytic enzymes, white-rot fungus has been recognized as playing an important role in the degradation of lignocellulose materials, which leads to the possibility of creating a composite enzymatic system with high hydrolysis efficiency in vitro. Echinodontium taxodii is a promising white-rot fungus for biologic pretreatment. In this study, we extracted the extracellular products of E. taxodii under solid-state fermentation conditions, mixed the extracellular products with cellulase to build a composite enzymatic system, and systematically evaluated the effect of this system on the hydrolysis of acid-pretreated and raw maize stovers. We found that the extracellular products from E. taxodii could significantly improve the hydrolysis efficiency of cellulase, with a synergistic action between the extracellular products and cellulase. Corn stovers treated with extracellular products were suitable for the enzymatic hydrolysis of cellulase. Furthermore, we found that pure proteins from the extracellular products were not sufficient to generate synergistic action. This finding suggests that non-protein substances may also be involved in the synergistic action between the extracellular products and cellulase.